From Byron to bin Laden : a history of foreign war volunteers - Arielli, Nir, 1975- (Harvard University Press, 2018)
What makes people fight and risk their lives for a country other than their own? Why did diverse individuals such as the poet Lord Byron, the writer George Orwell, the Argentinean revolutionary Che Guevara, and the young Saudi extremist Osama bin Laden all turn to foreign military service? From Byron to bin Laden makes a historian's examines the phenomenon of war volunteers who have travelled abroad to fight on the basis of a personal decision, without being sent by their governments and not strictly for the sake of material gain. Although fighting for very different causes, these volunteers shared a number of commonalities; they tended to superimpose their beliefs and perceptions on the wars they joined, while a personal search for meaning invariably underlined their actions. Through a comprehensive study of the history of foreign volunteering from the wars of the French Revolution to the present, the book opens up a broad range of questions that relate to individual motivations, ideology, gender, state-citizen relations, international law, military significance, radicalization and the memory of war.--